Identification of a functional variant in the KIF5A-CYP27B1-METTL1-FAM119B locus associated with multiple sclerosis. - Alcina, Antonio; Fedetz, María; Fernández, Óscar; Saiz, Albert; Izquierdo, Guillermo; Lucas, Miguel; Leyva-Fernández, Laura; García-León, Juan Antonio; Abad-Grau, María del Mar; Alloza, Iraide; Antigüedad, Alfredo; Garcia-Barcina, María Jesús; et al. (BMJ Journals, 2013)
Background and aim: Several studies have highlighted the association of the 12q13.3-12q14.1 region with coeliac disease, type 1 diabetes, rheumatoid arthritis and multiple sclerosis (MS); however, the causal variants underlying diseases are still unclear. The authors sought to identify the functional variant of this region associated with MS. Methods: Tag-single nucleotide polymorphism (SNP) analysis of the associated region encoding 15 genes was performed in 2876 MS patients and 2910 healthy Caucasian controls together with expression regulation analyses. Results: rs6581155, which tagged 18 variants within a region where 9 genes map, was sufficient to model the association. This SNP was in total linkage disequilibrium (LD) with other polymorphisms that associated with the expression levels of FAM119B, AVIL, TSFM, TSPAN31 and CYP27B1 genes in different expression quantitative trait loci studies. Functional annotations from Encyclopedia of DNA Elements (ENCODE) showed that six out of these rs6581155-tagged-SNPs were located in regions with regulatory potential and only one of them, rs10877013, exhibited allele-dependent (ratio A/G=9.5-fold) and orientation-dependent (forward/reverse=2.7-fold) enhancer activity as determined by luciferase reporter assays. This enhancer is located in a region where a long-range chromatin interaction among the promoters and promoter-enhancer of several genes has been described, possibly affecting their expression simultaneously. Conclusions: This study determines a functional variant which alters the enhancer activity of a regulatory element in the locus affecting the expression of several genes and explains the association of the 12q13.3-12q14.1 region with MS.
Keywords: Esclerosis múltiple; multiple sclerosis